A spatial beam property analyzer based on dispersive crystal diffraction for low-emittance X-ray light sources - Nazanin Samadi; Xianbo Shi; Cigdem Ozkan Loch; Juraj Krempasky; Michael Boege; Dean Chapman; Marco Stampanoni (Scientific Reports, 2022)
Abstract The advent of low-emittance synchrotron X-ray sources and free-electron lasers urges the development of novel diagnostic techniques for measuring and monitoring the spatial source properties, especially the source sizes. This work introduces an X-ray beam property analyzer based on a multi-crystal diffraction geometry, including a crystal-based monochromator and a Laue crystal in a dispersive setting to the monochromator. By measuring the flat beam and the transmitted beam profiles, the system can provide a simultaneous high-sensitivity characterization of the source size, divergence, position, and angle in the diffraction plane of the multi-crystal system. Detailed theoretical modeling predicts the system’s feasibility as a versatile characterization tool for monitoring the X-ray source and beam properties. The experimental validation was conducted at a bending magnet beamline at the Swiss Light Source by varying the machine parameters. A measurement sensitivity of less than 10% of a source size of around 12 µm is demonstrated. The proposed system offers a compact setup with simple X-ray optics and can also be utilized for monitoring the electron source.